Densification and Resistance of Ta2O5 and ZnO Co-doped SnO2 Ceramic Targets for Low-cost TCO Films of Solar Cells - Ning Jian; Jiwen Xu; Guisheng Zhu; Fei Shang; Huarui Xu (Materials Research)
SnO2-based TCO films can decrease the cost of solar cells, but its corresponding ceramic targets are difficult to sintering densification. Therefore, Ta2O5 and ZnO are used to enhance the density and conductivity of targets. The targets have rutile phase structure, dense microstructure and fine grains. The 0.85 wt% ZnO and 3 wt% Ta2O5 doped target sintered at 1500 °C achieve high relative density (>99%) and low resistance (< 50 Ω). The as-designed targets contribute to depositing SnO2-based TCO films by magnetron sputtering.